35-th Winter School on Wave and Quantum Acoustics - BUKOWSKI, Roman (Archives of Acoustics, 2006)
Ustroń, 27-th February - 3-rd March 2006I have a great pleasure to give the "Archives of Acoustics" Readers possibility acquaint with topics presented at 35-th Winter School on Wave and Quantum Acoustics. This School, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, is planned at February/March 2006 in beautiful scenery of Silesian Beskidy Mountains.As always, the School has been a place where achievements of various sections of acoustics (especially molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, acoustoelectronics, photoacoustics, acoustics of solids etc.) are being exchanged. Moreover, some similar and related topics, for example optoelectronics and thermal wave methods, will be presented too.For the second time the School will be divided on three different, but complementary, parts - Winter Workshops (WW). Chronologically it will be: 2-nd WW on Acoustoelectronics and Optoelectronics (chairman: prof. Tadeusz Pustelny), 2-nd WW on Molecular and Quantum Acoustics (chairwoman: dr Marzena Dzida) and 11-th WW on Photoacoustics and Thermal Waves Methods (chairman: prof. Jerzy Bodzenta). This dividing was very well accepted by Participants.After acceptation by revivers the School lectures will be published in one of two journals - in Journal de Physique IV - Proceedings (which is published by EDP Sciences and covered in the ISI database) or in Journal of Molecular and Quantum Acoustics (annual journal published by Upper Silesian Division of the Polish Acoustical Society). Moreover, all Participants will obtain a folder with Program of the School and full set of the one page abstracts obtained by organizers.Once again we have taken pains to organize this conference taking into account the fact that it is an important event for acousticians, opticians and other Polish and foreign scientists. We hope that this reach conference program will gain acceptance and respect among its potential participants. We count on your numerous response and active participation.